2016
DOI: 10.1016/j.atherosclerosis.2016.07.899
|View full text |Cite
|
Sign up to set email alerts
|

Spermidine reduces lipid accumulation and necrotic core formation in atherosclerotic plaques via induction of autophagy

Abstract: Spermidine inhibits lipid accumulation and necrotic core formation through stimulation of cholesterol efflux, albeit without changing plaque size or cellular composition. These effects, which are driven by autophagy in VSMCs, support the general idea that autophagy induction is potentially useful to prevent vascular disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
51
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(55 citation statements)
references
References 54 publications
3
51
0
1
Order By: Relevance
“…The association between high spermidine uptake and reduced mortality is independent from confounding factors including age, sex, body mass index, consumption of alcohol or aspirin, metabolic syndrome, diabetes, physical activity, and socioeconomic status, as well as conventional dietary scores distinguishing healthy from unhealthy eating. These results confirm our long-lasting suspicion that spermidine has broad health-improving effects [2][3][4][5][6][7][8][9], based on our observation that nutritional supplementation of this polyamine can extend the longevity of multiple model species, including yeast, nematodes, flies and mice [10][11][12]. Here, we explore the literature linking spermidine to reduced cancer risk.…”
supporting
confidence: 77%
“…The association between high spermidine uptake and reduced mortality is independent from confounding factors including age, sex, body mass index, consumption of alcohol or aspirin, metabolic syndrome, diabetes, physical activity, and socioeconomic status, as well as conventional dietary scores distinguishing healthy from unhealthy eating. These results confirm our long-lasting suspicion that spermidine has broad health-improving effects [2][3][4][5][6][7][8][9], based on our observation that nutritional supplementation of this polyamine can extend the longevity of multiple model species, including yeast, nematodes, flies and mice [10][11][12]. Here, we explore the literature linking spermidine to reduced cancer risk.…”
supporting
confidence: 77%
“…Spermidine reversed age-induced arterial stiffness with a reduction in oxidative damage of endothelial cells in old mice (65) and alleviated the formation of atherosclerotic plaques in apolipoprotein E-deficient (ApoE −/− ) mice fed a high-fat diet (HFD) for 20 weeks (66). In Dahl salt-sensitive rats fed a high-salt diet (a model of hypertensive heart failure), oral supplementation of spermidine reduced high blood pressure and delayed the transition to heart failure (44), further documenting the antihypertensive (67) and vascular health-promoting (65, 66) functions of dietary spermidine.…”
Section: Spermidine In Cardiovascular and Muscle-related Diseasementioning
confidence: 99%
“…Moreover, spermidine fails to promote cardioprotective effects in cardiomyocyte-specific Atg5 −/− mice (44) and does not restore stem cell-proliferative function in autophagy-deficient (Atg7 −/− ) Pax7-expressing cells (Pax7 represents a marker and regulator of muscle progenitors and satellite cells) (70). Last, the spermidine-mediated reduction of atherosclerotic lipid accumulation and necrotic core formation that is normally observed in ApoE −/− mice is absent in ApoE −/− Atg7 −/−deficient (autophagy-incompetent) animals (66).…”
Section: Autophagy and Mitophagy Induction Through Spermidine Adminismentioning
confidence: 99%
“…13) Spermine suppresses LFA-1, which binds to endothelial cells through interaction with Intercellular Adhesion Molecule 1 (ICAM-1), and is involved in the transmigration of inflammatory cells to sites of inflammation on human lymphocytes. 14) LaRocca et al 43) reported that spermidine exerts a potent anti-aging influence on arteries by increasing nitric oxide bioavailability, reducing oxidative stress, modifying structural factors, and enhancing autophagy. Recently, it was reported that cardiovascular diseases, including atherosclerosis, can be prevented by autophagy that is induced by spermidine in rodent experiments.…”
Section: Polyamines and Cardiovascular Diseases Including Atherosclementioning
confidence: 99%